Morphological characterization and comparison of coronary arterial trees - Bulant, C. A.; Blanco, P. J.; Assunção Jr, A. N.; Liberato, G.; Lima, T. P.; Parga Filho, J. R.; Lemos, Pedro A.; Ávila, L. F. R.; Feijóo, A. R. (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2014: Anais do XIV Workshop de Informática Médica, 2014)
In this work we propose the core work-flow for characterizing and comparing coronary trees from a geometrical point of view. The ultimate goal of this procedure is to develop a set of computational tools that can be used to estimate the likelihood of two heart vasculatures, and therefore be able to establish a similarity criteria between them.